Optimation of β-mannanase production on submerged culture of Eupenicillium javanicum as well as pH and temperature enzyme characterizations - T Purwadaria; T Haryati; E Frederick; B Tangendjaja (Indonesian Center for Animal Research and Development (ICARD), 2003)
Two successive experiments were conducted to determine the optimal substrate concentration of coconut meal (CM) and incubation time for production of β-mannanase from Eupenicillium javanicum. Both experiments were designed based on factorial. In the first experiment, the main factor was substrate concentration of 1, 2, and 3%, while the sub-factor was incubation time of 1, 2, 3, 4, 5, 6, and 7 days. The two factors were interacted highly significantly (P<0.01). Since the highest β- mannanase activity, protein concentration and saccharification activity towards coconut meal were obtained from 3% CM after five day incubation time (P<0.05), the second experiment was designed for higher substrate concentration. The main factor was also substrate concentration of 3, 4 and 5%, while the sub factor was incubation time of 5 and 6 days. The two factors were also interacted highly significantly (P<0.01) for mannanase activity and protein concentration, while specific activity was not significantly different (P>0.05). The best activity was obtained at 4% of coconut meal for five day incubation time, which was not significantly different with that of 3% at the same incubation time. Therefore, it was concluded from both experiments that the best enzyme production was obtained from 3% of coconut meal at incubation time of 5 days. Then, further experiments show that the enzyme had optimum pH at the range of 5.4-5.8, the same pH range in duodenum, while at pH 4.5 the activity was relatively low. Although, at pH 4.5 the enzyme activity was reduced, the enzyme was still active for four hours. At pH 5.8 and 6.5 the enzyme was quite stable. The optimum temperature of the enzyme was at 500C, higher than the body temperature of most poultry (400C). The reduction of enzyme activity at 400C could be overcome by increasing the enzyme concentration. The enzyme was stable after 4 hour incubation at 28 (room temperature) and 400C, however, the enzyme activity was considerably reduced at temperature of 900C after 60 second incubation. In the poultry digestion system the activity is not affected by temperature, but in the pelleting process where the steam temperature approximately 900C has to be limited for not more than 30 seconds. Key words: Coconut meal, β-mannanase, Eupenicillium javanicum, pH and temperature characterization